The use of novel xenografting methods to reveal differential gene expression between breast cancer at primary and metastatic sites - de Sousa, E; Emma de Sousa (2012)
In developed countries, breast cancer is the commonest malignancy among women. Understanding the mechanisms involved in breast cancer progression and the influence of the microenvironment on cancer cell proliferation, results in better treatments. This study aimed to optimise breast cancer xenograft rates using a novel chamber developed for tissue engineering purposes. The established tumours were subjected to enzyme digestion, creating a single cell suspension, which was then injected into immunocompromised mice at primary, metastatic and intra-cardiac sites. The resulting tumours in the mammary fat pad (MFP) and bone were compared using species-specific reverse-transcription polymerase chain reaction (RT-PCR) and cDNA microarray, to examine the influence of the microenvironment on gene expression. The achieved xenograft graft rates of 25% were similar to those previously reported. The matrix metalloproteinase family of enzymes (MMPs) degrade extracellular matrix, influencing invasion and migration of malignant cells. RT-PCR results showed that the majority of the MMPs expressed in the cancers were stromal rather than tumour in origin. MT1-MMP, MMP-2 and MMP-11 had significantly higher expression levels in the MFP than in the bone, but MMP-9 was expressed more in the bone than MFP. There was also an up-regulation of stromal production of MT1-MMP and MMP-13 in the MFP in the presence of tumour. This may have significance when considering which MMPs are the most appropriate targets for inhibition during cancer treatment. The most significant of the differentially expressed genes on microarray analysis were trefoil factor 1 (TFF1) and insulin growth-factor binding protein 3 (IGFBP-3), both expressed significantly more in tumours from the MFP than the bone. The thesis presented demonstrates some of the complexities of tumour-stromal interactions and supports Paget’s seed-soil theory, confirming in several ways the variation in gene expression in breast cancer between primary and metastatic sites.